Developing an Educational Program to Prevent Online Loan Problems Among Teachers and Students - Sriningsih, Riry (Fakultas MIPA Universitas Negeri Padang, 2025)
The problem of online loans has become an increasingly worrying phenomenon in Indonesia. Online loans have become a popular financial solution, but they pose risks such as high interest rates, data security threats, and psychological stress due to debt. Teachers and students are groups that are vulnerable to being affected by this problem, both directly and indirectly. This article discusses the development of an education program for teachers and students at SMKN 2 Padang Panjang, West Sumatra. The aim is to increase financial literacy in order to prevent the negative impacts of online loans among teachers and students. This program is designed through a participatory approach involving seminars, training/workshops, and financial simulations. The results show that structured education can improve financial online loans, financial literacy, education programs, financial management skills and awareness of the dangers of illegal online loans.